2013
DOI: 10.1111/raq.12042
|View full text |Cite
|
Sign up to set email alerts
|

Is dietary taurine supplementation beneficial for farmed fish and shrimp? a comprehensive review

Abstract: Taurine is a neutral β‐amino acid derived from the metabolism of sulphur‐containing amino acids. It is present in high concentrations in animal tissues, especially heart, retina, skeletal muscle, brain, large intestines, plasma, blood cells and leucocytes. Therefore, this amino acid plays significant roles in many physiological functions, including membrane stabilization, antioxidation, detoxification, modulation of immune response, calcium transport, myocardial contractility, retina development, bile acid met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 103 publications
(261 reference statements)
3
106
0
3
Order By: Relevance
“…First, the growth rate of sea cucumbers in this study was low, so the beneficial effect of taurine on the growth of sea cucumbers was not expressed. Second, previous studies suggested that beneficial effects of taurine on the growth of aquatic animals were especially obvious during early life stages of these animals (El‐Sayed ). In this study, sea cucumbers were juveniles and the beneficial effects of taurine may be more obvious in the seedling stage of sea cucumbers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the growth rate of sea cucumbers in this study was low, so the beneficial effect of taurine on the growth of sea cucumbers was not expressed. Second, previous studies suggested that beneficial effects of taurine on the growth of aquatic animals were especially obvious during early life stages of these animals (El‐Sayed ). In this study, sea cucumbers were juveniles and the beneficial effects of taurine may be more obvious in the seedling stage of sea cucumbers.…”
Section: Discussionmentioning
confidence: 99%
“…Taurine (2‐aminoethanesulfonic acid) is an amino sulfonic acid, which has been proved to be conditionally essential for some aquatic animals when these animals are fed diets containing high plant protein levels, as taurine is deficient in plant‐based protein sources (El‐Sayed ). In aquatic vertebrates, numerous studies have confirmed that dietary taurine could promote growth of some marine finfish species (Gaylord et al ; Lunger et al ; Takagi et al ; Yun et al ; Jirsa et al ; Wang et al ) and soft‐shelled turtles (Hou et al ) when fishmeal was replaced with plant proteins in the diets.…”
mentioning
confidence: 99%
“…Comparatively, the experimental winter feed (WF) had a much higher proportion of marine-derived protein sources (45.8%), consequently lower level of plant-proteins and the totality of the oil fraction associated to fish oil and krill phospholipids. This WF diet was further supplemented with betaine as a phagostimulant (Kasumyan & Døving, 2003; Kolkovski, Arieli & Tandler, 1997), soy lecithin to facilitate fat emulsification during digestion and/or improve lipid clearance from the gut (Koven et al, 1993; Koven et al, 1998; Tocher et al, 2008), vitamin C and vitamin E as antioxidants and non-essential amino acid taurine, given its role as antioxidant and involvement on bile acid conjugation (El-Sayed, 2013). The WF diet contained 50.6% crude protein, 19.7% crude fat, 22.4 kJ/g gross energy.…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, averaged over NSP level, fat ADC was lowest for fish fed the FM diets. Many marine fish species have a low taurine synthesis capacity, creating a need for exogenous taurine, while exogenous taurine seems not required for many freshwater fish species (Divakaran, Ramanathan, & Ostrowski, 1992;El-Sayed, 2014). This result is not in line with the observation of Richard, Colen, and Aragao (2017) in Senegalese sole that fat ADC of a taurine-free PB diet significantly improved after taurine supplementation.…”
Section: F I G U R Ementioning
confidence: 99%